Heart failure medication treatment and prognosis: a retrospective cross-sectional study - Lin, Qiankai; Lv, Zongjie; Li, Daiyi; Ling, Qiao; Qiu, Sha; Lei, Xiaomei; Qin, Fang; Wang, Na (Frontiers in Pharmacology, 2025)
ObjectiveHeart failure (HF) is a significant global public health concern and the leading cause of morbidity and mortality worldwide, imposing a substantial economic burden on society. Guideline-directed medical therapy (GDMT) refers to the standardized pharmacological treatment for specific diseases based on recommendations from authoritative clinical guidelines and evidence from large-scale randomized clinical trials. GDMT serves as the cornerstone of drug therapy for heart failure patients. This study describes hospitalized HF patients and focuses on drug prescription and readmission rates.MethodsThis study is a retrospective cross-sectional study with data from HF patients obtained from the Second Affiliated Hospital of Chongqing Medical University between January 2016 and June 2021. Patients were considered to have received GDMT if they were prescribed any guideline-recommended medication. Multilevel logistic regression was used to obtain the relationship between medication and readmission rates. The odds ratios (ORs) and 95% confidence intervals (CIs) have been reported.ResultsIn this study, a total of 5,356 HF patients (51.0% female; average age 77 years) were included. Among these patients, the most commonly used medications were mineralocorticoid receptor antagonists (MRA) (69.3%), Beta-blockers (54.2%), and lipid-lowering agents (46.0%). Currently, GDMT recommendations mainly include five types of drugs: diuretics, angiotensin receptor-neprilysin inhibitors (ARNIs), renin-angiotensin system inhibitors (ACEIs/ARBs), beta-blockers, mineralocorticoid receptor antagonists (MRAs), and sodium-glucose cotransporter-2 inhibitors (SGLT-2i). Among them, the utilization rates of ARNIs, SGLT-2i, triple therapy, and quadruple therapy are relatively low, accounting for 12.7%, 8.1%, 33.2%, and 3.75% respectively. The usage rates of these drugs are gradually increasing, especially after pharmacists participate in clinical decision-making and assist doctors in selecting therapeutic drugs, leading to a significant increase in the utilization rates of guideline-recommended drugs. Additionally, a multivariate logistic regression analysis of all drugs recommended by GDMT showed that ARBs (OR 0.681, CI 0.511–0.908), ARNIs (OR 0.191, CI 0.089–0.406), anticoagulants (OR 0.578, CI 0.403–0.829), tolvaptan (OR 0.340, CI 0.124–0.929), and SGLT-2i (OR 0.238, CI 0.058–0.969) significantly reduced the readmission rate of patients. Further subgroup analysis showed that the efficacy of the drugs varied slightly depending on the type of HF, but was consistent with guideline recommendations and clinical study results.ConclusionIn our hospital, the utilization rate of guideline-recommended drugs is gradually increasing, especially after pharmacists participate in rational drug use in clinical practice, the rate of increase is more significant, which is more in line with GDMT recommendations. Additionally, despite some limitations in our study, most of the guideline-recommended drugs show good therapeutic effects. And, we found that drugs such as SGLT-2i and ivabradine, despite their low usage rates, also demonstrate good therapeutic effects, providing significant implications for clinical decision-making.